CT images with expert manual contours of thoracic cancer for benchmarking auto‐segmentation accuracy. Issue 12 (1st March 2021) - Yang, Jinzhong; Veeraraghavan, Harini; van Elmpt, Wouter; Dekker, Andre; Gooding, Mark; Sharp, Greg
Abstract : Published in Medical Physics, Vol. 47, No. 7